The global burden of low back pain: estimates from the Global Burden of Disease 2010 study. Issue 6 (24th March 2014) - Hoy, Damian; March, Lyn; Brooks, Peter; Blyth, Fiona; Woolf, Anthony; Bain, Christopher; Williams, Gail; Smith, Emma; Vos, Theo; Barendregt, Jan; Murray, Chris; Burstein, Roy; et al.
Abstract : Objective: To estimate the global burden of low back pain (LBP). Methods: LBP was defined as pain in the area on the posterior aspect of the body from the lower margin of the twelfth ribs to the lower glutaeal folds with or without pain referred into one or both lower limbs that lasts for at least one day. Systematic reviews were performed of the prevalence, incidence, remission, duration, and mortality risk of LBP. Four levels of severity were identified for LBP with and without leg pain, each with their own disability weights. The disability weights were applied to prevalence values to derive the overall disability of LBP expressed as years lived with disability (YLDs). As there is no mortality from LBP, YLDs are the same as disability-adjusted life years (DALYs). Results: Out of all 291 conditions studied in the Global Burden of Disease 2010 Study, LBP ranked highest in terms of disability (YLDs), and sixth in terms of overall burden (DALYs). The global point prevalence of LBP was 9.4% (95% CI 9.0 to 9.8). DALYs increased from 58.2 million (M) (95% CI 39.9M to 78.1M) in 1990 to 83.0M (95% CI 56.6M to 111.9M) in 2010. Prevalence and burden increased with age. Conclusions: LBP causes more global disability than any other condition. With the ageing population, there is an urgent need for further research to better understand LBP across different settings.